Supercritical biharmonic equations with power-type nonlinearity - KARAGEORGIS, PASCHALIS (My University, 2009)
We study two different versions of a supercritical biharmonic equation with a power-type nonlinearity. First, we focus on the equation Delta(2)u = vertical bar u vertical bar(p-1)u over the whole space R(n), where n > 4 and p > (n + 4)/(n - 4). Assuming that p < p(c), where p(c) is a further critical exponent, we show that all regular radial solutions oscillate around an explicit singular radial solution. As it was already known, on the other hand, no such oscillations occur in the remaining case p >= p(c). We also study the Dirichlet problem for the equation Delta(2)u = lambda(1 + u)(p) over the unit ball in R(n), where lambda > 0 is an eigenvalue parameter, while n > 4 and p > (n + 4)/(n - 4) as before. When it comes to the extremal solution associated to this eigenvalue problem, we show that it is regular as long as p < p(c). Finally, we show that a singular solution exists for some appropriate lambda > 0
PUBLISHED
Keywords: supercritical biharmonic equation; power-type nonlinearity